(untitled) (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2022)
The pandemic that the world is going through due to COVID-19 exposed some of the main deficiencies of the Mexican educational system, among which the lack of dynamism to adapt to adverse contextual conditions stands out. Therefore, this article proposes to return to the components and principles of the Strategic Educational Management Model proposed by the Ministry of Public Education (SEP ) in 2010, to serve as the basis for the development of a rapid response plan that guarantees the right to education. quality education and allow students to adapt to socio-cultural changes by building the necessary new normalities.